The Urgency of Good Faith Principles in Production Sharing Cooperation Contracts with the Gross Split System - Szyva Silviana Putri; Gunardi Lie; Moody Rizqy Syailendra Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
With the existence of a production sharing contract carried out by the Government with contractors, it is possible to realize equitable energy in Indonesia. Gross Split itself will not eliminate State control in controlling oil and gas. The urgency of applying the principle of good faith in production sharing contracts with the gross split system is very important, with the hope of creating justice for business actors, which is a reflection of the principle of good faith in production sharing contracts with the gross split system, which illustrates that the principle of good faith is very important. important in making agreements, and in making contracts or cooperation must be based on the good faith of both parties in achieving common goals. So it is hoped that the application of this principle in production sharing contracts will be able to have a good impact on the development of the investment world in Indonesia which is increasingly advanced, and avoid losses for both parties.